Modified female mid‐urethral sling for the treatment of incontinence after prostate treatment: One‐center experience. Issue 5 (31st January 2022) - Mao, Qiqi; Lin, Yiwei; Xia, Dan; Wang, Shuo; Jiang, Hai
Abstract: Background: The male sling has emerged as a minimally invasive option for incontinence after prostate treatment (IPT) in recent years, but it has not yet been introduced into China. This study retrospectively evaluated the clinical outcomes of the modified female mid‐urethral sling in the treatment of IPT and explored potential preoperative factors to better predict surgical outcomes. Methods: From May 2014 to January 2021, a total of 70 patients with IPT who underwent transobturator male sling procedure using the modified female mid‐urethral sling were retrospectively reviewed. All surgeries were performed by a single surgeon. Functional outcomes were evaluated by daily pad usage, and the severity of incontinence was classified as mild (≤2 pads), moderate (3−4 pads), or severe (≥5 pads). Success was defined as no pad usage or 1 pad for safety (cure), or a reduction in daily pad use by >50% (improved). Patients were followed up at 3, 6 months, and yearly thereafter. Results: At a final follow‐up of 6−80 months, 35 (50.0%) patients were cured, 12 (17.1%) were improved, and 23 (32.9%) were still incontinent. There was a slight trend of declining continence over time, and the majority of patients remained improved. During follow‐up, 25 patients had perineal or scrotal pain, five patients had voiding difficulty and two had de novo urgency, one developed infection and underwent sling explantation. Early urinary retention was the only significant factor linked to better surgical outcomes. Conclusion: The modified female mid‐urethral sling represents a viable option for the treatment of IPT. Improved efficacy is seen in patients with a history of early postoperative urinary retention.